Single-Crystal 31P and 7Li NMR of the Ionic Conductor LiH2PO4 - Otto E. O. Zeman (Crystals, 2020)
The electronic surroundings of phosphorus and lithium atoms in the ionic conductor lithium dihydrogen phosphate (LDP) have been studied by single-crystal nuclear magnetic resonance (NMR) spectroscopy at room temperature. From orientation-dependent NMR spectra of a large homegrown LDP single crystal, the full 31P chemical shift (CS) and 7Li quadrupole coupling (QC) tensor was determined, using a global fit over three rotation patterns. The resulting CS tensor is characterized by its three eigenvalues: <semantics> <msubsup> δ 11 P A S </msubsup> = ( 67.0 ± 0.6 ) </semantics> ppm, <semantics> <msubsup> δ 22 P A S </msubsup> = ( 13.9 ± 1.5 ) </semantics> ppm, and <semantics> <msubsup> δ 33 P A S </msubsup> = ( − 78.7 ± 0.9 ) </semantics> ppm. All eigenvalues have also been verified by magic-angle spinning NMR on a polycrystalline sample, using Herzfeld–Berger analysis of the rotational side band pattern. The resulting 7Li QC tensor is characterized by its quadrupolar coupling constant <semantics> χ = <msubsup> Q 33 P A S </msubsup> = ( − 71 ± 1 ) </semantics> kHz and the two eigenvalues <semantics> <msubsup> Q 11 P A S </msubsup> = ( 22.3 ± 0.9 ) </semantics> kHz, and <semantics> <msubsup> Q 22 P A S </msubsup> = ( 48.4 ± 0.8 ) </semantics> kHz. The initially unknown orientation of the mounted crystal, expressed by the orientation of the rotation axis in the orthorhombic crystal frame, was included in the global data fit as well, thus obtaining it from NMR data only.